Devils' advocates : the hidden story of Rudy Giuliani, Hunter Biden, and the Washington insiders on the payrolls of corrupt foreign interests - Vogel, Kenneth P., 1975- (William Morrow, an imprint of HarperCollins, 2025)
"New York Times investigative reporter Kenneth P. Vogel exposes Washington's hidden world of foreign influence--the billion-dollar industry where lobbyists, consultants, and power brokers profit by advancing the agendas of dictators, oligarchs, and corrupt regimes. Drawing on extensive reporting, confidential documents, and insider sources, Vogel uncovers how these actors quietly shape U.S. foreign policy for personal gain. From Kyiv to Capitol Hill, he reveals the morally compromised deals, political scandals, and shadowy networks that sell access and influence at the expense of democracy and human rights."--